2012
DOI: 10.1016/j.ccr.2012.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Emergent Mutations in NAEβ Confer Resistance to the NEDD8-Activating Enzyme Inhibitor MLN4924

Abstract: MLN4924 is an investigational small-molecule inhibitor of NEDD8-activating enzyme (NAE) in clinical trials for the treatment of cancer. MLN4924 is a mechanism-based inhibitor, with enzyme inhibition occurring through the formation of a tight-binding NEDD8-MLN4924 adduct. In cell and xenograft models of cancer, we identified treatment-emergent heterozygous mutations in the adenosine triphosphate binding pocket and NEDD8-binding cleft of NAEβ as the primary mechanism of resistance to MLN4924. Biochemical analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 24 publications
4
84
1
Order By: Relevance
“…Our results showed that MLN4924 had significant and similar single-agent activity in both cisplatin-sensitive and -resistant models, indicating that the mechanisms that underlie resistance to cisplatin and MLN4924 likely do not overlap. This is in agreement with 2 recently published studies that identified treatment-related hetereozygous mutations in the ATP-binding pocket and NEDD8-binding cleft of NAEb as a novel mechanism of resistance to MLN4924 (12,38). Additional evidence for potentially distinct mechanisms of resistance between classical chemotherapy and MLN4924 is also provided by recent studies with MLN4924 in acute myelogenous leukemia (AML).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our results showed that MLN4924 had significant and similar single-agent activity in both cisplatin-sensitive and -resistant models, indicating that the mechanisms that underlie resistance to cisplatin and MLN4924 likely do not overlap. This is in agreement with 2 recently published studies that identified treatment-related hetereozygous mutations in the ATP-binding pocket and NEDD8-binding cleft of NAEb as a novel mechanism of resistance to MLN4924 (12,38). Additional evidence for potentially distinct mechanisms of resistance between classical chemotherapy and MLN4924 is also provided by recent studies with MLN4924 in acute myelogenous leukemia (AML).…”
Section: Discussionsupporting
confidence: 79%
“…1B). Notably, the variation in sensitivity of individual cell lines to MLN4924 was not due to mutations in NAEb, a recently identified mechanism of resistance to MLN4924, as DNA sequencing of all cell lines used in this study failed to detect any mutations (12).…”
Section: Mln4924 Diminishes Cell Viability and Impairs The Clonogenicmentioning
confidence: 93%
See 1 more Smart Citation
“…Nedd8 conditional KO also did not yield a productive model, since Nedd8 is required for cellular homeostasis. Therefore, in order to validate the results obtained with RNAi technology and establish the in vivo physiological relevance of neddylation during IL-1␤ production, we utilized an inhibitor of neddylation called MLN4924, which blocks the activity of Nedd8-activating enzyme (47)(48)(49). MLN4924 is currently being developed as an anticancer drug during tumorogenesis, since neddylation of the tumor suppressor protein p53 results in loss of its activity.…”
Section: Resultsmentioning
confidence: 99%
“…This was due to diminished processing of pro-caspase-1 to yield functional subunits (i.e., the p10 subunit). The knockdown studies were further validated by using MLN4924, a neddylation inhibitor that blocks the activity of Nedd8-activating enzyme (NAE) (47)(48)(49). Further studies revealed colocalization and coimmunoprecipitation of endogenous Nedd8 with caspase-1 in inflammasome-activated macrophages.…”
mentioning
confidence: 99%